Edukasi Pembuatan Dan Penggunaan Ramuan Jamu Saintifik Untuk Penyakit Hipertensi Di Kradenan Srimulyo Piyungan Bantul - kiki rizki; Fitri Yuliani (LPPM STIKES Madani, 2026)
Hypertension had been one of the most common non-communicable diseases whose prevalence had continued to increase among the elderly, requiring a complementary management approach based on scientific evidence. Scientific herbal medicine had been developed from traditional herbal formulations that had been scientifically tested for their efficacy and safety, making it suitable as a supportive therapy for hypertension control. This community service activity had aimed to improve the knowledge of elderly participants regarding the preparation and use of scientific herbal medicine for hypertension management through interactive lectures and the screening of educational videos. The activity had been conducted on June 28, 2025, at the Mosque of Kradenan Hamlet, Srimulyo, Piyungan, Bantul, involving 23 elderly participants from the local posyandu (community health post). Evaluation had been carried out using pretest and posttest methods consisting of ten true–false statements related to scientific herbal medicine and hypertension management. The results had shown a significant improvement in participants’ knowledge, where 91.3% had achieved an excellent category in the posttest compared to 0% in the pretest. The use of audiovisual media had proven effective in enhancing the elderly’s understanding of the concept of scientific herbal medicine, proper boiling techniques, and safe usage principles. This activity had contributed to improving health literacy among the elderly and encouraging the evidence-based and safe use of scientific herbal formulations as supportive therapy for hypertension control.